PTH Reloaded: A New Evolutionary Perspective - Suarez-Bregua, Paula; Cal, Laura; Cañestro, Cristian; Rotllant, Josep (Frontiers in Physiology, 2017)
The parathyroid hormone (PTH) family is a group of structurally-related secreted peptides involved in bone mineral homeostasis and multitude of developmental processes in vertebrates. These peptides mediate actions through PTH receptors (PTHRs), which belong to the transmembrane G protein-coupled receptor group. To date, genes encoding for PTH and PTHR have only been identified in chordates, suggesting that this signaling pathway may be an evolutionary innovation of our phylum. In vertebrates, we found up to six PTH and three PTHR different paralogs, varying in number between mammals and teleost fishes due to the different rounds of whole-genome duplication and specific gene losses suffered between the two groups of animals. The diversification of the PTH gene family has been accompanied by both functional divergence and convergence, making sometimes difficult the comparison between PTH peptides of teleosts and mammals. Here, we review the roles of all Pth peptides in fishes, and based on the evolutionary history of PTH paralogs, we propose a new and simple nomenclature from PTH1 to PTH4. Moreover, the recent characterization of the Pth4 in zebrafish allows us to consider the prominent role of the brain-to-bone signaling pathway in the regulation of bone development and homeostasis. Finally, comparison between PTH peptides of fish and mammals allows us to discuss an evolutionary model for PTH functions related to bone mineral balance during the vertebrate transition from an aquatic to a terrestrial environment.